2004
DOI: 10.1002/ange.200352803
|View full text |Cite
|
Sign up to set email alerts
|

Cleavable Linkers for Porous Silicon‐Based Mass Spectrometry

Abstract: Dippen – waschen – analysieren: Moleküle können durch Diels‐Alder‐Reaktionen an maßgeschneiderte poröse Silicium‐Wafer geknüpft und mit dem Laserpuls eines MALDI‐Massenspektrometers positionscodiert effizient abgelöst und detektiert werden (siehe Schema).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…Another method was presented by Meng et al (2004): in order to bind the substrate molecules, the surface of a DIOS chip was derivatized using special linkers, which are stable during the organic synthesis and cleavable during the LDI event. A similar approach was also adopted by Parker et al (2006); here, acrylamide‐labeled peptides were immobilized in a hydrogel surface and the enzymatic activity of a kinase was studied by detecting the phosphorylated peptides (Fig.…”
Section: On‐plate Chemistry and Biochemistrymentioning
confidence: 99%
“…Another method was presented by Meng et al (2004): in order to bind the substrate molecules, the surface of a DIOS chip was derivatized using special linkers, which are stable during the organic synthesis and cleavable during the LDI event. A similar approach was also adopted by Parker et al (2006); here, acrylamide‐labeled peptides were immobilized in a hydrogel surface and the enzymatic activity of a kinase was studied by detecting the phosphorylated peptides (Fig.…”
Section: On‐plate Chemistry and Biochemistrymentioning
confidence: 99%
“…However, Finn, Siuzdak, and co-workers have reported a related approach that employs cleavable linkers and may offer another route to high-throughput applications. 18,19 Additionally, the RapidFire method allows high-throughput analysis using mass spectrometry but requires a solid phase extraction or chromatographic sample preparation of the analyte before mass analysis. (4) With SAMDI, the array plates (384 spots) need only be rinsed and treated with matrix after analyte immobilization.…”
mentioning
confidence: 99%
“…7−9 Based on a similar fragmentation behavior observed for furan−maleimide adducts, this transition likely occurs via a retro DA (rDA) mechanism (Scheme 3). 43 Given this apparent labile nature of fulvene−maleimide adducts in the gas phase, we sought to determine if a similar fragmentation pattern would occur for conjugates without the presence of a photolabile group that might enable the development of a new class of mass tag reagents for biomolecule detection.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…At present, we could only find one other example where MS-induced rDA fragmentation has been exploited for the generation of mass tags, in which furan− maleimide adducts were utilized for monitoring enzymecatalyzed reactions of immobilized substrates on silicon chips using a MALDI-TOF instrument. 43 Despite their efficient fragmentation, the subdued reaction kinetics of furan− maleimide cycloadditions and reduced stability under physiological conditions limit their utility outside of organic synthesis. In contrast, we have shown that the fulvene−maleimide DA reaction can be used to rapidly generate protein bioconjugates in aqueous buffer at low temperatures and has facile fragmentation properties that enable mass tag detection in both MALDI and ESI experiments.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation